A benchmark study of the independent quality validation techniques of product design and development - Adeniji, Moyosore (Cranfield University, 2009)
As we move ahead in the 21st century, quality validation techniques need to be based on principles of long term safety as consumers are now more aware of safety issues surrounding product design and development and globalisation has brought about competition within the manufacturing industry. Quality is seen as a reality for all manufacturing organisations and if quality standards are ever compromised, the immediate benefits in terms of cost savings, efficiencies and enhanced profitability are often lost. The study aims to capture and analyse the industrial best practices of independent quality techniques to evaluate and validate product design and development. The project introduces various techniques used in testing hardware components of products and what the pros and cons of these testing techniques are. Due to the information that was to be gathered during the research process, an inductive approach was taken. This approach consisted mainly of five major phases; the literature and industrial research, data collection & analysis at the sponsor company, the benchmark study, the final proposal and validation of the project by experts at the sponsor company. Academic literature and various online resources were consulted and reviewed to identify the various hardware testing techniques and for overall insight into the common issues and challenges faced by manufacturing organisations involved in the use of the identified testing techniques. Comparisons were made between academic literature and reality in industry. The results revealed that the sponsor company was operating within the best practices of the manufacturing industry and conclusions were drawn from the entire study stating that although the sponsor company was operating within the best practices, there was room for improvement. The documented benefits of the testing techniques will provide factual information to the senior management team enabling them make strategic decisions on the new techniques that could be implemented into their hardware testing plan.
Keywords: quality validation techniques; product design; safety issues; testing techniques; hardware components; new techniques